Memahami Kekerasan Seksual dalam Menara Gading di Indonesia - Ariani Hasanah Soejoeti; Vinita Susanti (Jurnal Community, 2020)
Many studies on campus sexual assault in the past use lifestyle-routine activities theory to explain the crime. According to those studies,  certain lifestyle factors can increase the likelihood of victimization while still in college. Our research shows that the two theories fail to explain that several institutional policies or regulations set by universities can limit and shape an individual's lifestyle, thus increasing the risk of victimization. These policies or regulations include class schedules, thesis consultancies, and campus-community service programs. Against this background, the authors argue that the root cause of campus sexual assault lies in the patriarchal culture in the Indonesia context hence women have a higher risk of victimization than men.